PENGARUH BRAND COMMUNICATION, SERVICE QUALITY DAN BRAND PERSONALITY ANGGOTA DEWAN TERPILIH MELALUI BRAND TRUST TERHADAP BRAND LOYALTY PEMILIH (Studi Partai Politik Gerindra) - Arenggoasih, Wuri (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2016)
AbstractTalking about marketing communications today is not only to products but has penetrated into the political field. Indonesia as a democratic state which is to become the member of parliament needs to have as many voters and a strong loyalty to the sustainability of the council itself and the political parties. Brand Communication, Service Quality and Brand Personality emerged as a voter votes for member of parliament which gives the possibility of influence in building Brand Loyalty (loyalty) through Brand Trust (trust).The theory used is the Strategy Choice Theory suggests one of the forms Compliance Gaining which argued about strategies of verbal / non verbal and emphasized specific results loyalty. This research has shown that Brand Communication, Service Quality and Brand Personality as a real form of strategies verbal / nonverbal become voter votes for member of parliament which influence the Brand Loyalty through Brand Trust as a mediating variable.Keyword : marketing communications, Brand Communication, Service Quality, Brand Personality, Brand Loyalty, Brand Trust